Hair testing and doping control in sport - Kintz, P. (Toxicology letters, 1998)
The standard in drug testing for doping control is gas chromatography/mass spectrometry conducted on a urine sample. For the past 20 years, hair analysis has been proposed for identifying drug abusers in forensic science. Specimens can be collected under close supervision without embarrassment and are not subject to evasive maneuvers. In contrast with urine, hair analysis has a wide window of detection, ranging from weeks to months, depending on the length of the hair shaft, and provides information concerning the pattern of an individual's drug abuse. Hair analysis is not yet recognized by the International Olympic Committee, although this technology is accepted in most courts of Justice. In light of potential applications, hair should be included as a suitable specimen to document positive urine cases in doping control.